An Adolescents Health Seeking Information: A Systematic Review - Kharsynniang, Hamengamon (11th International Scholars Conference, 2024)
This study aims to identify adolescents’ health information sources and barriers to in-depth decision-making for educators and other stakeholders for adolescents’ well-being. A comprehensive literature search was conducted using electronic databases including PubMed, Mendeley, Scopus, and Google Scholar. Thematic analysis was used to categorize findings into common themes related to information sources, and barriers. Data extraction focused on study design, population characteristics, information sources, and barriers to health information seeking. The main sources of information used by adolescents in their daily lives were the Internet, peers and family, and health professionals. Among the barriers, quality of information, health professionals, lack of privacy and confidentiality, and internet literacy were common among adolescents. Adolescents’ search for health information is a complex problem that requires an advanced understanding of their requirements and habits. It is necessary to ensure that information is reliable, promote digital literacy, and create conditions that give teenagers the confidence to responsibly seek out and use health information through various platforms. By giving these factors top priority, we can assist teenagers in making knowledgeable health decisions and promoting healthier lives as they enter adulthood.